2021
DOI: 10.3390/coatings11101156
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Ce3+-Doped Ni0.5Cd0.5Fe2O4 Nanoparticles by Sol–Gel Auto-Combustion Method

Abstract: Cerium (Ce)-doped Ni0.5Cd0.5CexFe2−xO4 (0.0 ≤ x ≤ 0.20) was synthesized using the sol–gel auto-combustion method. X-ray diffraction (XRD) analysis revealed that all the samples retained spinel cubic crystal structure with space group Fd3m at 800 °C. Crystal structure parameters, such as lattice constant, average crystallite size, and X-ray density were estimated from the major XRD (311) peak. Bulk density and porosity were also calculated. The average crystallite size was estimated to be in the range of 20–24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
(45 reference statements)
2
2
0
Order By: Relevance
“…The trivalent state XRD data suggested the formation of the Fe phase. Similar findings have been reported by a number of researchers [42][43][44][45][46][47]. These findings support the development of the FCC framework and single phase spinel structure.…”
Section: X-ray Diffraction Of Mfesupporting
confidence: 92%
See 1 more Smart Citation
“…The trivalent state XRD data suggested the formation of the Fe phase. Similar findings have been reported by a number of researchers [42][43][44][45][46][47]. These findings support the development of the FCC framework and single phase spinel structure.…”
Section: X-ray Diffraction Of Mfesupporting
confidence: 92%
“…A larger lattice constant was the result of an attempt to replace the smaller ionic radius of Fe 3+ ions with the larger ionic radius of Cd 2+ ions. 6 The observed slight shifting of diffraction peaks is caused by the rivalry between cationic metals for occupying tetrahedral sites (A) and octahedral sites (B), which leads to the creation of a lattice defect [44]. The formation of multiple peaks indi-cates the presence of a polycrystalline structure.…”
Section: X-ray Diffraction Of Mfementioning
confidence: 99%
“…Fourier Transform Infrared studies for cadmium substituted magnetite by Gillot et al showed that increasing Cd 2+ ion composition in cadmium ferrite, decreases the number of absorption bands [9]. The XRD analysis reported by Devmunde et al revealed the formation of a single phase cubic spinel structure and FCC framework, the XRD pattern reported by this group closely matched with the pattern obtained in our research work and similar results were reported by other researchers such as Surech et al Manojit et al and Ahmad et al [10][11][12][13]. Yadav et al and Abouhaswa et al reported that the addition of manganese ions (Mn 2+ ) to ferrite sample increases the magnetic saturation, but upon mixing with Cd 2+ ion, the formations of high resistivity, high permeability and low magnetic losses were revealed [14,15].…”
Section: Introductionsupporting
confidence: 91%
“…Similar to ferroelectric materials, through the ages, it has been easy for 3D and nanocrystalline ferromagnetic materials with high Tc and magnetic intensity to be achieved [10]. For example, Ahmad et [11]. In addition, nanograined La 0.7 Sr 0.3 MnO 3 (LSMO) and Nd 0.7 Sr 0.3 MnO 3 (NSMO) were produced using various methods.…”
mentioning
confidence: 99%